Perlindungan Anak dalam Perspektif H.R Muslim No. 4650 dan Pasal 76A UU No. 35 Tahun 2014 - Annisa Rosdianti; Tajul Arifin (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Child protection in Indonesia is not fully optimal, so bullying occurs in all age groups, especially children. Knowing legal protection by comparing H.R. Muslim No. 4650 and Article 76A of Law No. 35 of 2014 concerning Child Protection. The author takes a qualitative approach with a normative analysis of Islamic legal doctrines and positive legal provisions. The results of the study show that the prohibitions listed in Muslim Hadith No. 4650 and Law Number 35 of 2014 concerning Child Protection are a strong basis in efforts to protect every child which emphasizes the importance of maintaining dignity and rights among others. Despite the differences in the types of punishments imposed, both still aim to stop the occurrence of bullying in the future as one of the efforts to realize child protection.